Pulmonary arterial hypertension: sex-specific differences and outcomes - Noura Alturaif; Umberto Attanasio; Valentina Mercurio (Therapeutic Advances in Respiratory Disease)
Pulmonary arterial hypertension (PAH) is a progressive and life-threatening vascular disease characterized by increased pulmonary vascular resistance, leading to right ventricular failure and death. It has a higher prevalence in women than men, yet notable sex-based differences influence disease presentation, treatment response, and outcomes. This narrative review explores the distinct sex differences in PAH and their significant impact on prognosis. Data from major PAH clinical trials indicate that nearly 78.4% of participants are women. According to the REVEAL registry, the most common causes of PAH in women are connective tissue disease-associated PAH (CTD-PAH), idiopathic PAH (IPAH), and congenital heart disease-associated PAH (CHD-PAH). Women are often found to have better baseline right ventricular (RV) function and hemodynamics before treatment, as well as more favorable RV adaptation post-therapy. They also demonstrate a stronger response to endothelin receptor antagonists (ERA) and prostacyclins. Most notably, these factors contribute to better survival outcomes in women compared to men. In conclusion, significant sex-based differences exist in PAH, underscoring the need for personalized treatment approaches that consider sex-related factors. Future research should focus on optimizing therapeutic strategies to improve outcomes for both sexes.